Protein arginine methyltransferase 10 is required for androgen-dependent proliferation of LNCaP prostate cancer cells. Issue 9 (2nd September 2015) - Harada, Naoki; Takagi, Toshiki; Nakano, Yoshihisa; Yamaji, Ryoichi; Inui, Hiroshi
Abstract: Androgen receptor (AR) signaling is the master regulator of prostate cell growth. Here, to better understand AR signaling, we searched for AR-interacting proteins by yeast two-hybrid screening and identified protein arginine methyltransferase 10 (PRMT10) as one of the interacting proteins. PRMT10 was highly expressed in reproductive tissues, such as prostate. Immunostaining showed that PRMT10 was expressed in the nucleus of both epithelia and stroma of rat prostate. In human prostate cancer LNCaP cells, PRMT10 co-immunoprecipitated with AR in both the presence and absence of dihydrotestosterone (DHT). Knockdown of PRMT10 by siRNA decreased DHT-dependent LNCaP cell growth and induction of prostate-specific antigen, an AR-target gene, without apparent loss of AR. DHT decreased PRMT10 at both the mRNA and protein levels. The decrease in PRMT10 was canceled by knockdown of AR or an AR antagonist. These results indicate that PRMT10 plays an important role in androgen-dependent proliferation of prostate cancer cells. Graphical abstract: : Role of protein arginine methyltransferase 10 in prostate